2020
DOI: 10.1002/ctm2.40
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors for mortality among inpatients with COVID‐19 in Wuhan, China

Abstract: Coronavirus disease 2019 (COVID-19) has become the worldwide pandemic. Currently, COVID-19, caused by the novel coronavirus, has had outbreaks in more than 213 countries and regions around the world and has caused many deaths. As of 24 April 2020, more than 2.62 million people had been diagnosed worldwide, of whom more than 180 000 died from the virus. 1 This cohort included COVID-19 patients admitted to The Central Hospital of Wuhan on 1 January 2020 to 15 February 2020. Of the 660 participating inpatients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 7 publications
4
49
0
1
Order By: Relevance
“…In this meta-analysis, there were 40 studies with 24,377 patients used to assess the incidence of AKI in COVID-19 patients [ 5 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ]. We found that the incidence of AKI was 10 % (95 % CI 8%–13 %) in COVID-19 patients, but there was evidence of statistical heterogeneity among the studies, with I 2 = 98 %.…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis, there were 40 studies with 24,377 patients used to assess the incidence of AKI in COVID-19 patients [ 5 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ]. We found that the incidence of AKI was 10 % (95 % CI 8%–13 %) in COVID-19 patients, but there was evidence of statistical heterogeneity among the studies, with I 2 = 98 %.…”
Section: Resultsmentioning
confidence: 99%
“…The flow of studies through our meta-analysis is depicted in Figure 1 . A total of 76 studies with 31,067 patients were eventually included in our study ( 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 2,876 were taking anticoagulants. Heparin was used in 3 studies, 3 , 4 , 5 whereas the type of anticoagulant was not specified in the other 3 studies. 6 , 7 , 8 In one study, heparin was used in prophylactic doses, 4 whereas anticoagulation was used in therapeutic doses in 2 studies.…”
mentioning
confidence: 99%